2019
DOI: 10.1002/cncr.32328
|View full text |Cite
|
Sign up to set email alerts
|

Glioma incidence and survival variations by county‐level socioeconomic measures

Abstract: BACKGROUND: Multiple studies have reported higher rates of glioma in areas with higher socioeconomic status (SES) but to the authors' knowledge have not stratified by other factors, including race/ethnicity or urban versus rural location. METHODS: The authors identified the average annual age-adjusted incidence rates and calculated hazard ratios for death for gliomas of various subtypes, stratified by a county-level index for SES, race/ethnicity, US region, and rural versus urban status. RESULTS: Rates of glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 36 publications
2
57
0
Order By: Relevance
“…Although great progress in glioma treatment has been obtained in recent years, the results are still unsatisfactory and relapse happens in almost all patients . Cancer stem cells (CSCs) have been thought to be the root of tumor occurrence, metastasis, and recurrence .…”
Section: Introductionmentioning
confidence: 99%
“…Although great progress in glioma treatment has been obtained in recent years, the results are still unsatisfactory and relapse happens in almost all patients . Cancer stem cells (CSCs) have been thought to be the root of tumor occurrence, metastasis, and recurrence .…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies in the United States and Europe estimated statistically significant relative risks of glioma ranging from 1.1 to 1.2 when comparing high and low SES groups. 17 18 19 One study that analyzed race/ethnicity subtypes showed significantly lower incidence rates in Asia-Pacific countries of high SES compared with those of low SES. 19 High SES is associated with better access to treatment including surgery, chemotherapy, radiation, and other adjunctive options, which are associated with better survival rates.…”
Section: Discussionmentioning
confidence: 99%
“… 17 18 19 One study that analyzed race/ethnicity subtypes showed significantly lower incidence rates in Asia-Pacific countries of high SES compared with those of low SES. 19 High SES is associated with better access to treatment including surgery, chemotherapy, radiation, and other adjunctive options, which are associated with better survival rates. 20 21 In the present study, patients with low SES had less opportunity to undergo TMZ and operation and a higher risk of death compared with patients with high SES.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics are diffuse invasive growth of tumor cells, unclear boundaries, relatively unlimited proliferation, and high invasiveness, all of which seriously affect human health 3 . Despite advances in the treatment of gliomas, the 5-year survival rate of glioma patients remains low 4 . For advanced glioma patients, systemic chemotherapy is main form of treatment 5 .…”
Section: Introductionmentioning
confidence: 99%